Zur Wechselwirkung zwischen Fahrbahntextur und Laufstreifenmischung von Pkw-Reifen - Riehm, Patrick (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2023)
This work aims to gain an understanding of the interactions between tread compounds and surface texture on dry and wet road conditions. If, for example, a corundum surface, which is very well-established in the tire industry, is used on the tire test bench instead of a real track surface, for wet track conditions ranking inversions in the tested compounds occur.